Influence of autolyzed whole yeast and yeast components on broiler chickens challenged with salmonella lipopolysaccharide. (8th August 2019) - Ahiwe, E U; Abdallh, M E; Chang'a, E P; Al-Qahtani, M; Omede, A A; Graham, H; Iji, P A
ABSTRACT: The objective of this study was to assess the effect of dietary yeast products on broiler chickens challenged with salmonella lipopolysaccharide (LPS ). The chicks were divided into 8 treatments with 6 replicates and 9 birds per replicate. The treatments consisted of a positive control (PC ) [without supplementation and not challenged]; negative control (NC ) [without supplementation but challenged]; whole yeast and challenged; yeast cell wall and challenged; yeast glucan and challenged; yeast mannan and challenged; zinc bacitracin and challenged; and Salinomycin and challenged. Whole yeast or Yeast cell wall was included at 2.0 g/kg diet. Yeast glucan or mannan was added at 0.20 g/kg diet. Zinc bacitracin (ZNB ) and Salinomycin (SAL ) was included at 50 and 60 ppm, respectively. Dietary treatments had no effect ( P > 0.05) on feed intake (FI ) at day 10. Supplementation with yeast and its derivatives improved ( P < 0.05) body weight gain (BWG ) and feed conversion ratio (FCR ) on day 10. On days 24 and 35, LPS challenge declined FI, BWG, FCR, and flock uniformity (day 28) in the NC group compared to the PC group. Yeast products and antibiotics improved ( P < 0.05) FI, BWG, FCR, and flock uniformity in LPS-challenged birds. On day 24, spleen weight increased while bursa weight decreased in the NC group relative to the PC group; this effect was reversed ( P < 0.05) by feeding all yeasts and antibiotics. On day 24, application of all the dietary treatments ameliorated the changes observed in white blood cell, lymphocyte and monocyte counts as well as albumin and immunoglobulin G of NC birds. On day 35, all yeasts additives, ZNB and SAL improved ( P < 0.05) the meat yield of broilers challenged with LPS. In conclusion, supplementation of diets with yeast and its derivatives can ameliorate the negative effects of salmonella LPS challenge on broiler chicks, thus improving the performance, flock uniformity, and meat yield.